A Systematic Review on the Acoustic Performance of Nanocellulose-Modified Natural Fibers for Sound Insulation and Absorption Applications - Muchlisinalahuddin; Rusli, Meifal; Dahlan, Hendery; Mahardika, Melbi (Piston: Journal of Technical Engineering, 2025)
Noise pollution has become an increasingly concerning environmental issue, driving the development of sustainable acoustic materials as alternatives to conventional synthetic materials. This research conducts a systematic literature review on the acoustic effectiveness of natural fiber-based nanocellulose in sound isolation and absorption applications. The research method employs a qualitative approach with a comprehensive analysis of scientific publications from Scopus, Web of Science, ScienceDirect, and Google Scholar databases over the past ten years. The review results indicate that modification of natural fibers such as coconut coir, hemp fiber, banana pseudostem, and rice straw with nanocellulose at a concentration of 1-1.5% w/v is capable of improve sound absorption coefficients up to 0.7-0.9 in the 500-2000 Hz frequency range, comparable to synthetic materials such as fiberglass and mineral wool. This material demonstrates advantages in terms of dimensional stability improvement of 35-40%, lightweight density (150-300 kg/m³), balanced acoustic characteristics across a broad frequency spectrum, and biodegradable properties providing minimal environmental impact. The potential applications of this material are extensive in construction, automotive, and acoustic industries, with noise reduction capabilities of up to 8-12 dB. Despite facing challenges in raw material variability and production scalability, natural fiber and nanocellulose-based acoustic materials have promising prospects as sustainable solutions to global noise pollution problems with competitive performance against conventional materials.